Adalimumab and methotrexate is more effective than adalimumab alone in patients with established rheumatoid arthritis: results from a 6-month longitudinal, observational, multicentre study. Issue 10 (5th May 2006) - Heiberg, M S; Rødevand, E; Mikkelsen, K; Kaufmann, C; Didriksen, A; Mowinckel, P; Kvien, T K
Abstract : Objectives: To compare the effectiveness of adalimumab monotherapy and adalimumab and methotrexate (MTX) combination therapy in patients with established rheumatoid arthritis. Methods: Data from an ongoing longitudinal observational study in Norway were used to compare response to treatment with two different adalimumab regimens (monotherapy, n = 84; combination with MTX, n = 99). Patients were assessed with measures of disease activity, health status and utility scores. Within-group changes were analysed from baseline to follow-up at 3 and 6 months and the changes were compared between groups after adjustment for the propensity score. The groups were also compared for the proportions of patients achieving European League Against Rheumatism (EULAR) good response, Disease Activity Score (DAS)28 remission and treatment terminations. Results: The improvement from baseline was significant for all measures in the adalimumab and MTX group, but only for DAS28, joint counts, two Short-form Health Survey with 36 questions (SF-36) dimensions and patient's and investigator's global assessment in the monotherapy group. All between-group differences were numerically in favour of combination therapy and significant for C reactive protein, joint counts, DAS28, Modified Health Assessment Questionnaire, investigator's global assessment, four SF-36 dimensions and Short Form 6D at 6 months. More patients in the combination therapy group reached EULAR good response (p<0.001) and remission (p = 0.07). At 6 months, 80.8% of the patients in the combination therapy group and 59.5% in the monotherapy group remained on treatment (p = 0.002). More withdrawals in the monotherapy group were due to adverse events. Conclusions: Our results were consistent across several categories of end points and suggest that adalimumab combined with MTX is effective in patients with rheumatoid arthritis treated in daily clinical practice and is superior to adalimumab monotherapy.